Comparative Analysis of Different Root Canal Sealers’ Cytotoxicity to Human Cells - Ashtha Arya; M Hema; Guruprasad Uikey; Aparna Rai; Sukruti Suresh; Arindam Banik (Journal of Pharmacy and Bioallied Sciences)
Background: Because they create a hermetic seal, root canal sealers are essential to the effectiveness of endodontic therapy. One important aspect affecting these sealers’ biocompatibility and clinical results is their cytotoxicity. Materials and Methods: The cytotoxicity of three distinct root canal sealers—sealer A, which is resin-based; sealer B, which is calcium silicate-based; and sealer C, which is zinc oxide-eugenol-based—was assessed in this in vitro investigation. In 96-well plates, human fibroblast cells were cultivated and subjected to sealer eluates made at 10%, 25%, and 50% concentrations. The MTT test was used to evaluate cell viability at 24, 48, and 72 hours. A microplate reader was used to measure arbitrary absorbance values at 570 nm. Results: For the 10% concentration, the mean cell viability percentages at 24 hours were as follows: 65% for sealer A, 80% for sealer B, and 55% for sealer C. Cell viability dramatically dropped at higher doses (50%): Sealer A was 40%, sealer B was 60%, and sealer C was 30% (P < 0.05). When compared to sealers A and C, sealer B consistently showed the best cell survival after 72 hours, demonstrating greater biocompatibility. Conclusion: The calcium silicate-based sealer was the least harmful to human cells among the tested root canal sealers; it was followed by the resin-based and zinc oxide-eugenol-based sealers. These results imply that calcium silicate-based sealers would be a safer option for clinical use; nevertheless, more in vivo research is necessary to validate these findings.